Propaganda Buzzer dalam Iklan Digital Kontemporer: Strategi Komunikasi, Persepsi, dan Dampaknya - Nandito Nandito; Fiqri Udayana; Raul Rizki Muhammad Kemal; Muhamad Daffa Fauzan; Arfian Suryasuciramdhan (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
The phenomenon of buzzers in digital advertising has become a critical concern in contemporary communication dynamics, due to their role in spreading covert messages for commercial and political purposes. This study aims to analyze the persuasive strategies and communication tactics of buzzers, algorithmic amplification patterns, and audience perceptions toward the disseminated content. Using a qualitative method through a systematic literature review, the study identifies three dominant buzzer strategies: native advertising, pseudo-influencer testimonials, and clickbait-based disinformation. These are often amplified through algorithmic tactics such as bot networks, trending hashtags, and endorsements by constructed influencer personas. Findings show that buzzer content is effective when perceived as authentic and emotionally engaging, but tends to generate resistance once users detect manipulation. The study’s implications highlight the need for greater transparency in digital communication, regulation of sponsored content, and improved media literacy to mitigate disinformation and public distrust. The research also emphasizes the importance of ethical approaches in digital communication practices to safeguard democratic integrity and sustainable brand–public relationships.